REPRODUCTIVE HEALTH OF WOMEN THE REPUBLIC OF KHAKASSIA AND ITS INFLUENCE ON THE DEMOGRAPHIC SITUATION - Валентина Сергеевна Гладкая; Надежда Николаевна Медведева; Татьяна Григорьевна Захарова; Вера Людвиговна Грицинская (The Publishing House Medicine and Enlightenment, 2016)
The estimation of medical-demographic processes in the Republic of Khakassia. Studied the main demographic indicators: population, birth rate, total mortality, infant, parental and maternal, indices, characterizing and affecting the reproductive health of the population in the dynamics since 1990.